Special Issue on Run-Time Systems and Target Platforms for Functional Languages: Editorial. Issue 6 (5th February 2015) - Sperber, Michael; Augustsson, Lennart
<x content-type="archive" xml:space="preserve">Abstract</x> Compiling functional languages to the existing variety of platforms calls for sophisticated implementations of run-time systems. This special issue focuses on this often-neglected aspect. We volunteered to compile this special issue in 2012 and immediately started soliciting papers. The original call for papers covered native-code platforms as well as run-time systems originally designed for non-functional languages such as the Java Virtual Machine or the .NET Common Language Runtime.